Kualitas Pelayanan Jasa Wedding Organizer Terhadap Tingkat Kepuasan Pelanggan Di Vowever Wedding Organizer Denpasar Bali - Ni Wayan Meri Agustini; I Nengah Wirata; Ketut Arjaya (Journal of Event and Convention Management, 2022)
The quality of wedding organizer services on the level of customer satisfaction is a business effort in providing services in the world of weddings which is carried out to achieve customer satisfaction. Customers can assess the quality of wedding organizer services to determine the good and bad of the wedding organizer's business. By providing the best quality service, it will increase customer satisfaction at the Vowever Wedding Organizer Denpasar Bali. In this study the author aims to determine the quality of wedding organizer services to the level of customer satisfaction at the Vowever WeddingOrganizerDenpasarBali. This study usesquantitative descriptive data analysis techniques through a Likert scale approach that uses a questionnaire. The number of samples used in this study were 31 people consisting of all couples who got married in 2019-2021 at the Vowever Wedding Organizer Denpasar Bali.The results of this study indicate that the quality of wedding organizer services on the level of customer satisfaction at the Vowever Wedding Organizer Denpasar Bali is good or satisfactory with an average of 4.36. This is because there are several aspects of the service quality dimension that get quite low scores, such as: lack of communication with customers and the lack of options for selecting wedding vendors. So that the Vowever Wedding Organizer Denpasar Bali is expected to be able to provide better service quality to increase customer satisfaction, so that the Vowever Wedding Organizer Denpasar Bali is able to achieve the desired goals.